Bivariate Rational Interpolants with Rectangle-Hole-Structure (Journal of Computational Mathematics, 1999)
Bivariate vector valued rational interpolants are established by means of Thiele-type branched continued fractions and Samelson inverse over rectangular grids with holes, characterisation theorem with topologic structure is brought in light and uniqueness theorem in some sense is obatained .